TOXICITY AND REPELLENCY OF DIFFERENT INSECTICIDES AGAINST Heterotermes indicola (ISOPTERA: RHINOTERMITIDAE) - F. Manzoor; A. H. Sayyed; T. Rafique; S. A. Malik (Journal of Animal and Plant Sciences, 2012)
In Laboratory bioassays four Insecticides Imidacloprid, Chlorfenapyr, Bifenthrin, and Fipronil at concentrations 1.56, 3.125, 6.25, 12.50, 25, 50, 100 ppm andCadusafos at concentrations 0.098, 0.195, 0.391, 0.781, 1.562, 3.125 and 6.25 ppm were used to explore the feasibility of controlling the H. indicola, the toxicities and repellencies of these chemicals to the workers in the present study. Toxicity was expressed as F-1(0.97) for 8 hrs and one month old treated soil. For H. indicola when treated with Imidacloprid, Chlorfenapyr, Bifenthrin, and Fipronil it took more than 8 hours to obtain 97% mortality in 8 hrs and one month old treatments. LC50 values for H. indicola were 346.75, 75.86, 14.45, 1.05, 0.46 for Imidacloprid, Chlorfenapyr, fipronil, Bifenthrin, and Cadusafos, respectively after 8 hrs exposure and corresponding values after one month exposure the values were 1230.27, 190.5, 28.18, 10.47 and 2.51, respectively. Present study also reveals that Chlorfenapyr was non-repellent and Fipronil was repellent only above 25ppm and Bifenthrin was repellent at all tested concentrations.
Keywords: Toxicity; Mortality; H. indicola; Repellency; LC